Master-slave control and evaluation of force sensing for robot-assisted minimally invasive surgery. Issue 6 (13th August 2020) - Li, Kun; Ji, Shuai; Niu, Guojun; Ai, Yue; Pan, Bo; Fu, Yili
Abstract : Purpose: Existing robot-assisted minimally invasive surgery (RMIS) system lacks of force feedback, and it cannot provide the surgeon with interaction forces between the surgical instruments and patient's tissues. This paper aims to restore force sensation for the RMIS system and evaluate effect of force sensing in a master-slave manner. Design/methodology/approach: This paper presents a four-DOF surgical instrument with modular joints and six-axis force sensing capability and proposes an incremental position mode master–slave control strategy based on separated position and orientation to reflect motion of the end of master manipulator to the end of surgical instrument. Ex-vivo experiments including tissue palpation and blunt dissection are conducted to verify the effect of force sensing for the surgical instrument. An experiment of trajectory tracking is carried out to test precision of the control strategy. Findings: Results of trajectory tracking experiment show that this control strategy can precisely reflect the hand motion of the operator, and the results of the ex-vivo experiments including tissue palpation and blunt dissection illustrate that this surgical instrument can measure the six-axis interaction forces successfully for the RMIS. Originality/value: This paper addresses the important role of force sensing and force feedback in RMIS, clarifies the feasibility to apply this instrument prototype in RMIS for force sensing and provides technical support of force feedback for further clinical application.